In vitro evaluation of dental color stability using various aesthetic restorative materials after immersion in different drinks - Tavga Mustafa Faris; Rukhosh Hasan Abdulrahim; Mohammed Abdalla Mahmood; Gollshang Ahmad Mhammed Dalloo; Sarhang Sarwat Gul (BMC, 2023)
Abstract Background Currently, the demands for restorations have increased considerably; thus, improvements and modifications have been made in dental composite technologies especially using materials that have been claimed to improve color stability. Objective This study aimed to determine the effect of various solutions on the color stability of different restorative materials in vitro study. Methods This study used three types of esthetic restorative materials. The samples comprised 45 discs, including 15 micro-hybrids, 15 nano-hybrids, and 15 glass ionomers). These discs were immersed in various beverages an hour a day for one month at room temperature. The color stability was measured using a spectrophotometer before/after immersion (days 7 and 30). Results We realized a significant difference in color change with Coca-Cola and tea-milk solution after seven days and 30 days (p < 0.05). However, no significant difference was found in the samples immersed in DM after seven days and 30 days (p > 0.05). The highest value of lightness (∆L) and stainability (∆a) was seen in micro-hybrid after 30 days of immersion in tea-milk solution (− 12.16 ± 1.74 and 11.4 ± 3.82, respectively), while most samples had a positive ∆b value. Conclusion After one month, the tea-milk solution affected the color stability of all used restorative materials. In addition, micro-hybrid had higher color stability than nano-hybrid and glass ionomer.